Kontribusi Tingkat Penguasaan Konsep Menulis Terhadap Kemampuan Menulis Karangan Argumentasi Siswa Kelas X MA Negeri X Koto Singkarak Kabupaten Solok - Susanti Marisya; Noni Febriana (Fakultas Sastra Universitas Ekasakti, 2019)
Background of the problem of the research were: 1) writing an argumentation is a difficult thing for the students, 2) less interest of the students in writing argumentation, 3) students lack master and knowledge of good writing concepts. The pupose of this research is to find out how much the contribution of the master of writing concepts to the ability to write essays in class X MA Negeri X Koto Singkarak. Population of the correlation research is the students of into students of grade X MA Negeri X Koto Singkarak sub province of Solok year 2016/2017 with the total sample 40 students. Technique of the taking sample used is total sampling. Instruments of the research used are objective test of mastery of the writing concept and performance tests for writing essay arguments. This Research data in the form of score that have been converted into scores.Data analysis techniques by changing scores into grades. Testing requirements analysis (homogenety test normality test and linearity test) and hypothesis testing Pearson Product Moment (PPM). The Result of the research concluded that writing concept shows the significant contribution in 29,59% into writing ability of an argumentation. The findings of this research indicate that the hinger the level of master of syudent’ writinh concepts, the hinger the ability to write essays of argumentation. Therefore, The teacher is advised to pay attention to the master of students’ writing concepts and Gide encouragement to students to do writing avtivties so that their argument writing abilities improve.